A revision of the subgenus Leucandrena of the genus Andrena of eastern Asia (Hymenoptera: Apoidea: Andrenidae) - Xu, Huanli; Tadauchi, Osamu (Zootaxa, 2009)
The subgenus Leucandrena of the genus Andrena of eastern Asia is revised, and seven species are recognized. Two new species, Andrena (Leucandrena) paramelanospila and Andrena (Leucandrena) banchan are described from Beijing and Xizang (China) respectively, and the male of Andrena (Leucandrena) melanospila Cockerell is described for the first time. A. (Euandrena) taisetsusana Tadauchi et Hirashima, and A. (Andrena) dolharubang Tadauchi and Xu are recognized as new synonyms of the Holarctic A. barbilabris (Kirby). A key to East Asian Leucandrena is given.